2016
DOI: 10.1016/j.tig.2015.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Thinking: How Histone Modifications Regulate Gene Expression

Abstract: The DNA of each cell is wrapped around histone octamers, forming so-called 'nucleosomal core particles'. These histone proteins have tails that project from the nucleosome and many residues in these tails can be post-translationally modified, influencing all DNA-based processes, including chromatin compaction, nucleosome dynamics, and transcription. In contrast to those present in histone tails, modifications in the core regions of the histones had remained largely uncharacterised until recently, when some of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
491
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 708 publications
(526 citation statements)
references
References 337 publications
8
491
0
6
Order By: Relevance
“…Generally speaking, marks such as H3K4me3, H3K9ac and H3K27ac denote regions of active gene expression, and marks such as H3K9me2/3 and H3K27me3 denote regions of transcriptional repression (for review see refs. 27,28). Among the many known repressive epigenetic modifiers, the Ehmt1/2 complex plays a central part in establishing repressive epigenetic marks.…”
Section: The Ehmt1/2 Complexmentioning
confidence: 99%
“…Generally speaking, marks such as H3K4me3, H3K9ac and H3K27ac denote regions of active gene expression, and marks such as H3K9me2/3 and H3K27me3 denote regions of transcriptional repression (for review see refs. 27,28). Among the many known repressive epigenetic modifiers, the Ehmt1/2 complex plays a central part in establishing repressive epigenetic marks.…”
Section: The Ehmt1/2 Complexmentioning
confidence: 99%
“…Information other than that on the genetic level has been found to be related to a variety of biological phenomena such as gene expression and cell differentiation [20][21][22][23][24][25][26][27][28]. Histone modifications and replacements belong to such mechanisms [25,26,[29][30][31][32][33][34][35][36][37][38][39].…”
Section: Modification and Replacement For Histonesmentioning
confidence: 99%
“…Histone modifications and replacements belong to such mechanisms [25,26,[29][30][31][32][33][34][35][36][37][38][39]. A chromosome is formed from chromatin, which is modelled from histones and DNA [40,41].…”
Section: Modification and Replacement For Histonesmentioning
confidence: 99%
“…Current research work has shown DNA repair, replication, stemness and alteration in cell state are influenced as well by histone core modifications. In addition, histone modifications are directly regulating transcription (Lawrence et al, 2016).…”
Section: Histone Modification and Chromatin Remodellingmentioning
confidence: 99%